The prospects for early detection with optical coherence tomography (OCT) and OCT angiography in major depressive disorder - Xiao, Qian; Li, Fangling; Jiang, Furong; Zhang, Zhejia; Xu, Bei (Journal of affective disorders, 2024)
Research has shown the diagnostic potential of optical coherence tomography (OCT) and OCT angiography (OCTA) in various psychiatric disorders. However, there is few research focusing on changes specific to Major Depressive Disorder (MDD), and the diagnostic value of OCT combined with OCTA parameters for MDD remains unclear. In this study, we investigated microvascular and morphology changes in the retina of MDD patients using a combination of OCTA and OCT parameters, and to examine their correlation with MDD mood and cognitive function in order to assess their diagnostic capability. Our findings revealed a significant decline in macular vessel density (MVD) in the superficial retinal capillary plexus (SRCP) across all subfields, except the NO area. We also observed a significant positive correlation between fovea and Stroop-1, as well as between temporal inner (TI) and Stroop-3 in MDD patients. Furthermore, we identified a negative correlation between fovea and Self-Rating Depression Scale, as well as between Superior outer (SO) and Difficulties in Emotion Regulation Scale-C in MDD patients. The sample size was small. Anatomical variables in blood flow may contribute to variability between subjects and outcomes. The diagnostic value of OCTA suggests their potential as valuable tools for monitoring and diagnosing MDD. •A significant decrease in macular vessel density in the superficial retinal capillary plexus in MDD compared to healthy controls.•Positive correlation between fovea/ temporal inner and Stroop Color-Word Test in MDD.•Negative correlation between fovea and depressive symptom in MDD•The combined diagnostic potential of OCT and OCTA suggests their utility as valuable tools for diagnosing MDD.